Inefficiency in private value bargaining with naive players: An experimental study - Alexandre Possajennikov; Rene Saran (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2018)
The paper reports on an experiment on two-player double-auction bargaining with private values. We consider a setting with discrete two-point overlapping distributions of traders' valuations, in which there exists a fully efficient equilibrium. We show that if there are traders that behave naively, i.e., set bid or ask equal to their valuation, then there is no equilibrium achieving full efficiency. In the experiment, we vary the proportion of naive traders by introducing computerized players. We find that full efficiency is not achieved in the experiment with or without naive traders, and efficiency is not lower in the presence of naive traders. Subjects mostly set bid/ask prices strategically but the extent of strategic behavior is not larger in the presence of naive players. We can explain these results by a learning model of noisy strategy adjustment. We also find that framing the double auction as a direct mechanism leads to more naive behavior by experiment participants, and that allowing face-to-face pre-play communication increases efficiency although still not to the full level.
Keywords: C72; C78; C91; D82; 330; bargaining with private values; double auction; efficiency; honesty